2018
DOI: 10.1111/jasp.12533
|View full text |Cite
|
Sign up to set email alerts
|

Does functional diversity increase effectiveness of community care teams? The moderating role of shared vision, interaction frequency, and team reflexivity

Abstract: As interprofessional collaboration becomes more commonplace in health and social care, both scholars and practitioners are searching for ways to make the most out of functionally diverse teams. Earlier research has shown that the presence of different functional backgrounds may lead teams to perform better, because they have a larger pool of knowledge and experience to draw from. Other studies show, however, that functional diversity increases categorization, reduces team cohesion, and complicates interpersona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 70 publications
0
22
0
Order By: Relevance
“…During these transition phases, a team is primarily concerned with the evaluation of its performance and focuses on planning activities (Lyubovnikova et al , 2017). In their study of community care teams, Hofhuis et al (2018) found that open discussions about communication and cooperation made the best use of team members’ backgrounds.…”
Section: Literature Reviewmentioning
confidence: 99%
“…During these transition phases, a team is primarily concerned with the evaluation of its performance and focuses on planning activities (Lyubovnikova et al , 2017). In their study of community care teams, Hofhuis et al (2018) found that open discussions about communication and cooperation made the best use of team members’ backgrounds.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These outcomes of leader vision communication—creating a shared sense of purpose for the future and generating shared goals—should help teams see past surface‐level gender differences because team members will focus on the vision of the future and be motivated to work together to attain the leader's vision. Indeed, prior research finds that teams with a shared vision are able to overcome team diversity and leverage differences for the benefit of the team (Hofhuis et al., 2018). Further, leaders who communicate a vision will likely make demographic diversity less pertinent by getting employees to buy into a larger cause (Greer, Homan, De Hoogh, & Den Hartog, 2012) and share an ultimate goal (Carton et al., 2014).…”
Section: Gender Diversity and The Cemmentioning
confidence: 99%
“…Shared vision is defined as the degree to which team members have a clear picture of, and agree upon, the goals of the team [68]. For SIDRTs, team goals may be more diffused, due to the different functional frameworks within which the team members operate [69].…”
Section: Knowledge Interaction Environmentand Knowledge Interactionmentioning
confidence: 99%